The quality of motivation among elementary school students - Rufini, Sueli Édi; Bzuneck, José Aloyseo; Oliveira, Katya Luciane de (Paidéia (Ribeirão Preto), 2012)
Lack of motivation in students to learn is a pressing educational problem. This paper presents the results of an assessment of the quality of motivation of 1,381 elementary school students, with an average age of 11.2 years, through the application of the Elementary School Motivation Scale (Escala de Motivação de Estudantes do Ensino Fundamental). The results revealed that autonomous motivation predominated among the participants. The comparison among variables showed that a lack of motivation and controlled motivation were higher among the male participants in comparison to the females, who obtained higher rates in the evaluation of autonomous motivation. Controlled motivation and lack of motivation increased as students advanced in grades, while autonomous motivation decreased. Students at private schools were less self motivated and depended more on external control to become motivated when compared to students from the public system. The latter were significantly more involved in school for autonomous reasons. The educational implications of these findings are considered in the discussion session.